Serum C-reactive protein and C-reactive gene (-717C>T) polymorphism are not associated with periodontitis in Indonesian male patients - Antonius Winoto Suhartono; Benso Sulijaya; Niniarty Zeiroeddin Djamal; Sri Lelyati Chaidar Masulili; Christopher Talbot; Elza Ibrahim Auerkari (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Periodontitis is an inflammatory disease caused by periodontal pathogens and influenced by multiple risk factors such as genetics, smoking habit, age and systemic diseases. The inflammatory cascade is characterized by the release of C-reactive protein (CRP). Periodontitis has been reported to have plausible links to increased level of CRP, which in turn has been associated to elevated risk of  cardiovascular disease (CVD). Purpose: The purpose of this study was t o investigate the relationship amongst the severity of periodontitis, CRP level in blood and CRP (-717 C>T) gene polymorphism in male Indonesian smokers and non-smokers. Method: The severity of periodontitis was assessed for 97 consenting male Indonesian smokers and non-smokers. The CRP level of the subjects was determined by using immuno-turbidimetric assay performed in PARAHITA Diagnostic Center Laboratory ISO 9001: 2000 Cert No. 15225/2. The rate of CRP (-717C>T) gene polymorphism was determined by using PCR-RFLP in Oral Biology Laboratory, Faculty of Dentistry, Universitas Indonesia. Result: The results suggest that the CRP protein level is not significantly associated with the tested CRP gene polymorphism (p>0.05). Also, while the severity of periodontitis increased significantly with subject age, the CRP level in blood serum was not significantly related to the severity of  periodontitis. The genotypes of the tested polymorphism did not show significant association with the severity of periodontitis either in smokers or in the combined population including smokers and non-smokers. The results naturally do not exclude such associations, but suggest that to discern the differences the sample size must be considerably increased. Conclusion: The CRP (-717C>T) gene polymorphism and CRP level in blood serum were not found to be associated with the severity of periodontitis in male smokers or in the combined population of smokers and non-smokers.